NILAI-NILAI AGAMA ISLAM DALAM MENSUKSESKAN PROSES DAN MENGOPTIMALKAN HASIL LAYANAN BIMBINGAN DAN KONSELING - Ahmad Syarqawi (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2016)
Development and cultural shift has helped bring guidance and counseling services to a direction that more exist. Since 1900 guidance and counseling have been there, and the current guidance and counseling services is not the same applied to the services provided at the beginning of 1900. Guidance and counseling are always adjusting studies and models of service based on the demands of the times and the people who lived in his time.This time is a period that is always changing very fast, so for those who can not follow this change will be left behind and become a problem to be solved. Based on this phenomenon, it is important to integrate the values of Islam into the guidance and counseling services. This approach is an alternative to help clients who need guidance and counseling services.